Diamond Detectors for Timing Measurements in High Energy Physics - Bossini, Edoardo; Minafra, Nicola (Frontiers in Physics, 2020)
Timing detectors are a well established part of High Energy Physics experimental instrumentation. The choice of sensors with fast (less than 10 ns) and precise (better than 100 ps) signals is an essential part of the design of a timing detector, together with radiation resistance considerations. Single crystal diamond sensors are one of the most promising technologies in this field. In this paper, the main characteristics that make single diamond crystal sensors ideal for timing applications will be described and an introduction to the design of fast front-end electronics will be given. Finally, two examples of diamond timing detectors used in High Energy Physics, the START detector of HADES and the TOTEM/CMS timing detector, will be discussed.